Large-scale international volleyball competition in "bubble" under the COVID-19 pandemic - Tomofumi Nishino; Kazuhiro Obara; Yusuke Nishida; Hiroshi Yamaguchi; Mitsutoshi Hayashi; Masashi Yamazaki (Elsevier, 2022)
Objective: To verify whether a large-scale international volleyball competition could be conducted safely using the bubble method, both for our participating team and as a whole. Methods: All 32 men's and women's teams were gathered in one place and a large-scale international volleyball competition was held for over a month without spectators using the bubble method. More than 1,000 people participated in the event, and 572 volleyball players played a total of 248 matches during the competition. There were 54 participants from Japan, including 27 male and female staff and players each. There was one team doctor for both men and women. A total of 2,250 PCR tests and 7,920 antigen tests were performed over 38 days. We investigated the incidence of infection in our team and in all participating teams. Results: There were 9 fever cases from our men's team, but all of them tested negative for COVID-19. Overall, a total of 10,170 tests were performed and only one was positive. Conclusion: In order to ensure the health and well-being of all participants, the indoor competition was concluded safely without the occurrence of COIVD-19 clusters in the bubble system with strict adherence to various strict protocols of COVID-19.